Employment, spillovers and 'decent work': Challenging the Productivity Commission's auto industry narrative. (June 2016) - Barnes, Tom; Roose, Joshua M; Heap, Lisa; Turner, Bryan S
The 2013 and 2014 announcements by major car manufacturers that they would wind down all their remaining Australian automotive operations by 2016/2017 pre-empted the March 2014 release of the Productivity Commission's final report into motor vehicle manufacturing. The Commission suggested that government subsidies had only delayed car plant closures and reiterated its longstanding opposition to industry policy and redistributive regional adjustment programmes by government. Industrialists, employer associations, state governments and trade unions have, however, questioned the Commission's forecasts for both economic spillover effects and social impacts in regions affected by automotive plant closures. In addition to challenging several underlying assumptions used to calculate the Productivity Commission's forecasts, this article argues that insufficient attention has been paid to the quality of future work. It extends insights from previous studies of industrial decline by proposing a new research agenda based on the idea of 'social spillovers'.